2014
DOI: 10.1021/ie500686p
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the Effect of the Vapor Split Ratio Decision in Design on Operability for DWC by Numerical Simulation

Abstract: The effect of the vapor split ratio on the operability of divided wall column (DWC) is numerically investigated. Four DWCs for separating a three-component mixture with, respectively, four different compositions are designed and then simulated to show the dependence of a total annualized cost (TAC) of the columns on the vapor split ratio, r v , which is subjected to change in operation for reason for either the design uncertainty or the possible change in the feed composition. It is shown that the TAC is sens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 22 publications
0
19
0
Order By: Relevance
“…Because of the presence of the diving wall in the column, liquid splits from column section I into sections II and IV, and vapor splits from column section VI into sections III and V. Although many researchers have proposed different optimal design methods, few considered rigorously the impact of the vapor flow resistances of the column sections in the two sides of the dividing wall on the vapor split ratio, which has been shown to be extremely important for the economic performance of the DWC. 54 In particular, in most studies, 42,45,55 the pressure drops of all trays were assumed equal, and by assuming equal pressure drop on both sides, the number of trays is thus constrained to be equal as well. However, actually, an equal number of stages does not imply equal flow resistance due to the possible differences in vapor and liquid loads, the dividing wall position, and the types of column internals (trays, packings, etc.)…”
Section: Case Studymentioning
confidence: 99%
See 1 more Smart Citation
“…Because of the presence of the diving wall in the column, liquid splits from column section I into sections II and IV, and vapor splits from column section VI into sections III and V. Although many researchers have proposed different optimal design methods, few considered rigorously the impact of the vapor flow resistances of the column sections in the two sides of the dividing wall on the vapor split ratio, which has been shown to be extremely important for the economic performance of the DWC. 54 In particular, in most studies, 42,45,55 the pressure drops of all trays were assumed equal, and by assuming equal pressure drop on both sides, the number of trays is thus constrained to be equal as well. However, actually, an equal number of stages does not imply equal flow resistance due to the possible differences in vapor and liquid loads, the dividing wall position, and the types of column internals (trays, packings, etc.)…”
Section: Case Studymentioning
confidence: 99%
“…Once the number of trays is determined for each column section, the locations of the feed and side draw are also determined. Because of the presence of the diving wall in the column, liquid splits from column section I into sections II and IV, and vapor splits from column section VI into sections III and V. Although many researchers have proposed different optimal design methods, few considered rigorously the impact of the vapor flow resistances of the column sections in the two sides of the dividing wall on the vapor split ratio, which has been shown to be extremely important for the economic performance of the DWC . In particular, in most studies, ,, the pressure drops of all trays were assumed equal, and by assuming equal pressure drop on both sides, the number of trays is thus constrained to be equal as well.…”
Section: Case Studymentioning
confidence: 99%
“…A steady state DWC had five independent operating variables including the liquid split ratio (r L ) and vapor split ratio (r V ) to the prefractionator, the reflux rate (R), the side product rate (S) and the distillate product rate (D). [28,29] R, S and D get fixed by product purity constraints on the distillate, side product, and bottoms product streams. The remaining variables, r L and r V were the unconstrained operating variables and can be used to get the minimum reboiler duty.…”
Section: Design Of Optimal Dwcmentioning
confidence: 99%
“…However, the vapor split ratio is usually a fixed variable predetermined in the initial design. The vapor flows are, usually, divided by positioning the dividing wall and controlling cross-sectional areas of the two column sides . However, devices and control structure have been proposed to improve the vapor split ratio. For example, Kang et al suggested the vapor control by a modified chimney tray with a specially designed cap, which can be controlled by its liquid level in both sections of the dividing wall.…”
Section: Introductionmentioning
confidence: 99%
“…However, devices and control structure have been proposed to improve the vapor split ratio. For example, Kang et al suggested the vapor control by a modified chimney tray with a specially designed cap, which can be controlled by its liquid level in both sections of the dividing wall. The total annual cost (TAC) of a DWC depends on both the liquid and vapor split ratios, and these variables can be manipulated to achieve the best separation efficiency. ,, According to Ge et al, for any given feasible vapor split ratio, there is a corresponding liquid split ratio that minimizes the TAC value. Additionally, the optimum split ratio depends on the feed composition. , …”
Section: Introductionmentioning
confidence: 99%